Diftéria--výsledky imunologického prehĺadu - Lancová, J; Miková, I (Epidemiologie, mikrobiologie, imunologie, 2002)
The objective of the immunological survey (IS) was in addition to assessment of the overall immunity of the Slovak population against diphtheria to test the effectiveness of vaccination and suitability of the used vaccination pattern and to assess the persistence of antibodies against diphtheria in more advanced age, and possibly the need of revaccination. The sera were tested by means of the neutralization test on cell cultures. The level of diphtheria antitoxin was assessed quantitatively. In the reaction standards were used--diphtheria toxin 79/1 1000 Lf, produced in the National Institute of Public Health and the Environment Bilthoven, Netherlands and the diphtheria antitoxin Diphtheria antitoxin equine British Standard 66/153, obtained from WHO International Laboratory for Biological Standards, Great Britain. The overall immunity assessed on a nationwide scale in Slovakia was adequate (88.2%). In the child population the level of antibodies correlated well with the administration of individual vaccinations against diphtheria. In 6- to 10-year old children the serum positivity was as high as 100%, in older children it did not drop below 95%. A more marked decline of serum positivity was found in the population above 40 years. The highest proportion of sensitive subjects was in the group of 50-59-year-old ones (45.2%). The antidiphtheritic immunity of the population under 50 years is very good. Inadequate immunity of adults above 50 years revealed the need of administering a booster dose against diphtheria which will have a positive impact on the antibody level of this age group of the population.
Keywords: protilátky bakteriální; dospělí; Infant; dítě; předškolní dítě; Adult; vakcinace; Adolescent; Slovakia; difterie; lidé; Corynebacterium diphtheriae; Antibodies, Bacterial; Vaccination; kojenec; Aged; Child, Preschool; Diphtheria; lidé středního věku; Child; Slovenská republika; senioři; Middle Aged; mladiství; Humans